SEBARAN DAN UKURAN KOLONI SARANG RAYAP POHON Nasutitermes sp (ISOPTERA: TERMITIDAE) DI PULAU SEBESI LAMPUNG SEBAGAI SUMBER BELAJAR BIOLOGI - Kuswanto, Eko; Pratama, Anisa Oktina Sari (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
Research on the distribution and colony size of nests of Nasutitermes sp. (Isoptera: Termitidae) have been conducted in Sebesi Island, Lampung. The method used in this study is a direct observation on the northern coast Sebesi Island. The results showed there were 60 nests of termite Nasutitermes sp. on the nine hosted tree species, i.e. Spandias sp., Leucaena leucocephala, Cocos nucifera, Caesalpinia pulcherrima, Moringa oleifera, Rhizophora apiculata, Delonix regia, Pandanus sp., and Morinda citrifolia. These termite nests vary in size. Direct counting on two nests indicates that colony size of Nasutitermes sp. on the nest sized 0.00828 m3 were 20,192 individuals and on the nest sized 0.1756 m3 were 35,086 individuals.The result of the the research gives contribution source of learning material in biology learning.Â Kata Kunci: Nasutitermes sp, rayap pohon, sebaran, ukuran sarang Â